Smallholders’ knowledge about healing goat gastrointestinal parasite infections with wild plants in southern DR Congo - Mavungu, Gaël Nzuzi; Mutombo, Cedrick Shakalenga; Numbi, Désiré Mujike; Nsenga, Salvatora Nkulu; Muyumba, Welcome Nonga; Pongombo, Celestin Shongo; Bakari, Salvius Amuri; Nachtergael, Amandine; Vandenput, Sandrina; Okombe, Victor Embeya; Duez, Pierre (Frontiers in Pharmacology, 2023)
Gastrointestinal parasite (GIP) infections control has an important role to play in increasing livestock production from a limited natural resource base and to improve animal health and welfare. This study aimed to collect indigenous knowledge and identify wild plants locally used by goat smallholders of three territories of Haut-Katanga province for treating signs of gastrointestinal parasitism. Ethnoveterinary surveys were conducted by semi-structured interviews and a bibliographic screening of the biological activities relating to cited plants was carried out. Our interviews indicate that ethnosemantic diagnoses of GIP diseases are based on signs. Eighty-seven informants reported that 27 plant species from 15 families, dominated by Fabaceae (29.6%) and Lamiaceae (18.5%) are commonly used in their goats treatment. Among these plants, five species with palmately compound leaves are considerably more used. From those, we noted a substitution of Vitex congolensis De Wild (Lamiaceae) by Oldfieldia dactillophylla (Welw. Ex Oliv.) J. Leonard (Picrodendraceae) and of Vitex mombassae by Vitex madiensis. Roots (46.9%), leaves (28.0%) and seeds (12.5%) are the most frequently used plant organs, and maceration is applied for most of the medicinal preparations (62.2%). Recipes are administered by oral route, for GIP (i) prevention (33.3%), by macerating the ground plant material in drinking water for two weeks at the start of each season (dry and rainy); and (ii) treatment (66.7%). According to the literature, some of these plants have few or no studies investigating their anthelmintic activity. The cited plants are worth investigating further as they could constitute an effective alternative strategy in maintaining animal productivity. Studies on the biological activity of these plants can also provide indications of promising leads for extracts that could be developed into commercial standardized medications.